Rational emotive behavioral education model to reduce aggressive behavior in adolescents - Khairunnisa, Isti Widya; Isti'adah, Feida Noor Laila; Sugara, Gian Sugiana (Jurnal Konseling dan Pendidikan, 2024)
Aggressive behavior is behavior that is manifested in the form of destroying objects or attacking other people verbally or non-verbally. This research tested the effectiveness of the Rational Emotive Behavior Education Model in reducing aggressive behavior in 36 class XI students at SMKN 2 Tasikmalaya. The selected students had high levels of aggressive behavior based on the Buss-Perry Aggression Questionnaire (BPAQ) scale. The experimental study with Time Series Design was conducted for 5 weeks, with one REBE intervention session per week for 40-60 minutes. The results showed a significant decrease in overall aggressive behavior scores from pre-intervention (M = 104.35) to post-intervention (M = 84.94). A significant decrease was also observed in the scores of each dimension of aggressive behavior, namely physical (29.93 to 24.42), verbal (17.68 to 14.24), anger (25.94 to 21.25), and hostility (30.49 to 24.64). These results indicate that REBE is effective in reducing aggressive behavior in students, helping them to think rationally, reducing emotional disturbances, increasing self-understanding, developing more adaptive coping strategies, and improving self-concept and sense of responsibility.